The 2017 coastal El Niño - Takahashi, Ken (2018)
The original concept of El Niño consisted of anomalously high sea surface temperature and heavy rainfall along the arid northern coast of Peru (Carranza 1891; Carrillo 1893). The concept evolved into the El Niño–Southern Oscillation (ENSO; Bjerknes 1969), although the original El Niño and the Southern Oscillation do not necessarily have the same variability (Deser and Wallace 1987), and the strong El Niño episode in early 1925 coincided with cold-to-neutral ENSO conditions (Takahashi and Martínez 2017). To distinguish the near-coastal El Niño from the warm ENSO phase, Peru operationally defines the “coastal El Niño” based on the seasonal Niño 1+2 SST anomaly (ENFEN 2012; L’Heureux et al. 2017). While recent attention has been brought to the concept of ENSO diversity (e.g., “central Pacific” vs “eastern Pacific” events; Capotondi et al. 2015), the coastal El Niño represents another facet of ENSO that requires further study in terms of its mechanisms and predictability.